2005
DOI: 10.1111/j.1365-2222.2004.02197.x
|View full text |Cite
|
Sign up to set email alerts
|

The human leucocyte antigen‐DRB1*1302‐DQB1*0609‐DPB1*0201 haplotype may be a strong genetic marker for aspirin‐induced urticaria

Abstract: SummaryBackground Urticaria/angioedema is a common aspirin-induced allergy; however, its pathogenic mechanism is not understood. Objective In order to uncover the genetic mechanism, we studied the associations of the human leucocyte antigen (HLA) genotypes in patients with aspirin-induced urticaria compared with aspirinintolerant asthma and normal control in a Korean population. Methods Ninety-four aspirin-induced urticaria patients presenting urticaria/angioedema-induced by both ASA and NSAID (50 had underlyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(46 citation statements)
references
References 19 publications
2
38
0
3
Order By: Relevance
“…We have demonstrated an association between HLA genotype and AIU by using a high-resolution analysis technique, confirming a strong positive association between the HLA DRB1 Ã 1302 and HLA DQB1 Ã 0609 alleles in AIU [14 ]; allelic frequencies of HLA DRB1 Ã 1302 and HLA DQB1 Ã 0609 were significantly higher in AIU patients than in AIA patients or in normal control subjects (Table 1). When clinical parameters were analyzed according to the presence of these two alleles, the patients carrying HLA DRB1 Ã 1302 or HLA DQB1 Ã 0609 (28.2 AE 7.0 and 29.0 AE 6.9 years respectively) were significantly younger (by 10 years) than those without either allele (38.0 AE 13.6 and 36.4 AE 13.4 years respectively), indicating that patients with these alleles develop AIU at an earlier age.…”
Section: Hla Gene Markers For Patients With Aspirin-induced Urticariasupporting
confidence: 70%
“…We have demonstrated an association between HLA genotype and AIU by using a high-resolution analysis technique, confirming a strong positive association between the HLA DRB1 Ã 1302 and HLA DQB1 Ã 0609 alleles in AIU [14 ]; allelic frequencies of HLA DRB1 Ã 1302 and HLA DQB1 Ã 0609 were significantly higher in AIU patients than in AIA patients or in normal control subjects (Table 1). When clinical parameters were analyzed according to the presence of these two alleles, the patients carrying HLA DRB1 Ã 1302 or HLA DQB1 Ã 0609 (28.2 AE 7.0 and 29.0 AE 6.9 years respectively) were significantly younger (by 10 years) than those without either allele (38.0 AE 13.6 and 36.4 AE 13.4 years respectively), indicating that patients with these alleles develop AIU at an earlier age.…”
Section: Hla Gene Markers For Patients With Aspirin-induced Urticariasupporting
confidence: 70%
“…Finally, further associations have been found with the adenosine receptor A3 gene (-1050G>T and -564C>T) [117], IL4 (-589T>C) [112,118], IL10 (-1082 G>A) [112], CTLA (49A>G) [112], nitric oxide synthase 2 [119], and the HLA system [120][121][122].…”
Section: Other Variants Outside Eicosanoid Biosynthesismentioning
confidence: 99%
“…HLA-DRB1*1302-DQB1*0609 has also been recognized as a genetic marker for AIU. 3 Leukotriene overproduction may be one of the mechanisms responsible for AIU, 1,4 which is supported by genetic studies showing significant association of leukotriene C4 synthase (LTC4S) 5,6 and 5-lipoxygenase (ALOX5). 7 In addition, previous genetic association studies have reported that the IgE high affinity receptor (FCER1A), 8 histamine N-methyltransferase (HNMT) 9 and adenosine A3 receptor (ADORA3) 10 genes are genetic determinants of AIU, which indicates that genetic variation associated with increased histamine release and ⁄or augmented mast cell signalling, leading to the release of proinflammatory mediators, can contribute to the development of AIU.…”
Section: Discussionmentioning
confidence: 94%
“…AIU was defined by a positive result on an aspirin oral provocation test, which was performed using 500 mg of aspirin (Rhonal; KunWha Pharmaceutical Co., Seoul, Korea) as described previously. 3 Patients with AIU can be classified into two different phenotypes, AIAU and AICU. Aspirin is regarded as a causative factor of urticaria and ⁄or angio-oedema in AIAU, which lasts for < 6 weeks, whereas it exacerbates pre-existing urticaria in AICU, which lasts for more than 6 weeks.…”
Section: Study Subjectsmentioning
confidence: 99%